Translesion synthesis of the major nitrogen mustard-induced DNA lesion by human DNA polymerase η. Issue 23 (11th December 2020) - Jung, Hunmin; Rayala, Naveen Kumar; Lee, Seongmin
Abstract : Nitrogen mustards are among the first modern anticancer chemotherapeutics that are still widely used as non-specific anticancer alkylating agents. While the mechanism of action of mustard drugs involves the generation of DNA interstrand cross-links, the predominant lesions produced by these drugs are nitrogen half-mustard-N7-dG (NHMG) adducts. The bulky major groove lesion NHMG, if left unrepaired, can be bypassed by translesion synthesis (TLS) DNA polymerases. However, studies of the TLS past NHMG have not been reported so far. Here, we present the first synthesis of an oligonucleotide containing a site-specific NHMG. We also report kinetic and structural characterization of human DNA polymerase η (polη) bypassing NHMG. The templating NHMG slows dCTP incorporation ∼130-fold, while it increases the misincorporation frequency ∼10–30-fold, highlighting the promutagenic nature of NHMG. A crystal structure of polη incorporating dCTP opposite NHMG shows a Watson–Crick NHMG:dCTP base pair with a large propeller twist angle. The nitrogen half-mustard moiety fits snugly into an open cleft created by the Arg61–Trp64 loop of polη, suggesting a role of the Arg61–Trp64 loop in accommodating bulky major groove adducts during lesion bypass. Overall, our results presented here to provide first insights into the TLS of the major DNA adduct formed by nitrogen mustard drugs.